Media and Information Literacy Education in the Age of Disinformation: SEUU Professor and Student Perceptions - Demush Bajrami; Edlira PALLOSHI DISHA; Albulena Halili; Shemsedin Ibrahimi (Institute of Communication Studies, 2023)
We are living in the disinformation age or in that of a revolution in propaganda, which gives rise to fragile democracies, vulnerable citizens, less capable deliberations, new forms of subversion, misuse of information by third parties etc. North Macedonia is a highly fragmented and polarized society, which gives space to the impact of malign actors for achieving their geopolitical goals such as to destabilize, weaken ties with the West or just increase their presence. Resilience, thus, has become the shield of contemporary information warfare. Media and Information Literacy education through the development of critical thinking in the young generation is a conditio sine qua non for building resilience to disinformation. This study argues that universities as agents of change have the mission to lead the process of building societal resilience through Media and Information Literacy education. In this paper the researchers from the Media Literacy and Disinformation Research Cluster at Max van der Stoel Institute (MVDSI), South East European University (SEEU) through a mixed-method-approach based on both qualitative and quantitative methods, examine the perceptions of SEEU academic staff members and students regarding Media and Information Literacy education at the university level. Data from the staff questionnaire (n=45) suggest that the majority of academic staff members across all SEEU faculties and institutes perceive Media and Information Literacy education as one of the ways to make youth resilient to disinformation. Moreover, the student questionnaire (n=105) revealed similar results. SEEU students stated their desire for the introduction of Media and Information Literacy as an elective course in their curricula, as one of the best ways to become resilient to disinformation on the internet. Ways and modalities of implementation and course content remain objects of exploration.